"That's why now we have a pension". Workers and employers in El Sauzalito (Chaco, Argentina) in the 1970s (Quinto Sol, 2024)
During the 1970s, indigenous settlers (Wichí people) and non-indigenous people gathered around the area now known as El Sauzalito. They carried out work related to logging, village construction and agriculture. Here we analyze the relationship between them as workers and employers. The approach is done through the ethnographic method. Remembered and narrated interactions are contemplated, considering the modalities of payment to the workers, the administration of sales income, the coordination of activities, access to food and retirements/pensions. We find that the subordinate relationship of workers to employers can be interpreted both in terms of protection (employers do their part, workers treated as “employees”) and in terms of domination (employers don't do their part, workers treated like “changarines”).
Keywords: indigenous peoples; employment; work; labour relations